2018
DOI: 10.1002/jcc.25191
|View full text |Cite
|
Sign up to set email alerts
|

Pt–Co nanocluster in hollow carbon nanospheres

Abstract: Recently, it has been reported that small Pt/Co bimetallic nanoclusters into hollow carbon spheres (HCS) show outstanding catalytic performances in deriving biomass fuels due to the small particle size and the homogeneous alloying. Thus, the knowledge about the thermal evolution and stability of the nanoclusters into the HCS has a great importance. We have simulated the heating process beyond the melting point for the bare and encapsulated Pt/Co clusters into the HCS with the different sizes of 55, 147, and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The same tendency ( i.e . a higher melting point of the confined phase related to free NP) was reported for Au–Pd–Pt NP confined in CNT and PtCo NP confined in hollow carbon spheres . For copper it was shown that the melting temperature of the NP decreases with decreasing CNT diameter.…”
Section: Why Anchoring Metal Nanoparticles Clusters or Metal Single A...mentioning
confidence: 79%
See 3 more Smart Citations
“…The same tendency ( i.e . a higher melting point of the confined phase related to free NP) was reported for Au–Pd–Pt NP confined in CNT and PtCo NP confined in hollow carbon spheres . For copper it was shown that the melting temperature of the NP decreases with decreasing CNT diameter.…”
Section: Why Anchoring Metal Nanoparticles Clusters or Metal Single A...mentioning
confidence: 79%
“…715,721 It has been clearly demonstrated that these structural changes of confined species has a direct impact on the properties of the NP. The thermal stability of Al, 722 Au, [723][724][725] Au-Pt, 726 Cu, 727,728 Pd, 729 Pd-Pt, 730 Pd-Au-Pt, 731 PtCo, 732 PtCu, 733 or Pt 734 clusters located in the inner cavity of CNT or carbon nanospheres has been studied by MD calculations. In the case of gold, the melting phenomenon starts from the innermost layer, when the freezing one begins from the outermost layer for confined NP.…”
Section: Electronic or "Hard" Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 structural stability in comparison to bare Pt/Co nanoclusters. 50 Akbarzadeh et al, again through MD simulations, demonstrated that carbon capsulation of the nanoparticles is an effective way of increasing the thermal and structural stability of the HNPs. 51 Also, Akbarzadeh et al investigated the thermodynamic behavior of graphite-supported Ag NPs by MD simulations.…”
Section: ■ Introductionmentioning
confidence: 99%